High-speed rail services development and regional accessibility restructuring in megaregions: A case of the Yangtze River Delta, China. (December 2018) - Wang, Lei
Abstract: Many countries have planned to improve intercity links in megaregions by developing High-speed rail (HSR) projects. The development of HSR service network in megaregions can change accessibility landscapes and create advantaged and disadvantaged cities. This study investigates how HSR service development has restructured uneven regional accessibility by developing a new regional accessibility measurement to incorporate train service frequency into the prevailing speed-dominated calculations. We conduct a longitudinal study to examine the changing patterns and relevant determinants of regional accessibility in the Yangtze River Delta (YRD), China, as well as the differences between conventional rail (CR) cities and HSR cities. The results indicate that the development of HSR services network has enhanced regional accessibility in the YRD rather than having the overall effect of restructuring the existing accessibility patterns formed by CR services. It has reduced the disparity of regional accessibility but has widened the gap between HSR and CR cities and increased the disparity of CR cities. Combined with a Tobit regression analysis, the results suggest that HSR network development in the YRD was highly spatially selective towards the cities that had higher CR network accessibility and better economic development performance. However, the disadvantage of regional accessibility for CR cities remains persistent, which may result in the issue of 'peripheralisation of the periphery'. Some policy implications for an integration of the CR and HSR services for both CR and HSR cities are outlined in conclusion. Highlights: We investigate how HSR services development has restructured uneven regional accessibility by developing a new accessibility measurement. HSR services network has enhanced regional accessibility rather than having the overall effect of restructuring the existing patterns. HSR development was highly spatially selective towards cities that had higher CR network accessibility and better economic performance. The disadvantage of accessibility for CR cities remains persistent, which may result in the issue of 'peripheralisation of the periphery'.